Attitudes and aspirations regarding engineering among Chinese secondary school students: comparisons between industrialising and post-industrial geo-engineering regions of Mainland China and Hong Kong. Issue 4 (4th July 2018) - Kutnick, Peter; Zhu, Zhiyong; Chan, Cecilia; Chan, Rosanna Yuen-Yan; Lee, Betty Pok-Yee; Lai, Veronica Ka Wai
Abstract: School-based pipelines/routes for university and technical engineering education are recognised as important for economic development and the high-school years are critical for shaping students' career aspirations and attitudes. This study examined a range of attitudes/experiences on the aspirations of secondary students to pursue engineering education and vocation. Experiential/attitudinal aspects covered demographic characteristics, family/school support, practical learning experiences, curricular/extra-curricular experiences, attitudes, perceptions and engineering-efficacy that may affect aspirations. A validated questionnaire capturing these variables was administered to respective samples of secondary school students from four Chinese geo-engineering regions (Beijing, Guangzhou, Hong Kong and ShanXi; 5965 students) that represent differing degrees of industrialisation. Comparative analyses across regions show 'doing' engineering is key to motivating students' aspirations; while regional variations suggest that schooling and family factors are generally more significant in industrialising Mainland cities, and extracurricular opportunities and personal factors are more significant for students in post-industrial Hong Kong.